Radialni model angleškega predloga on v odnosu do slovenskega predloga na - Sicherl, Eva (Slavistična revija, 2007)
The article aims to show a construction of one of the possible radial models presenting the distribution of meaning of the English preposition on in relation to the Slovene preposition na. Slovene speakers of English tend to establish 100 % semantic equivalence between these two prepositions. The radial model suggests the extent to which semantic equivalence between these two prepositions is indeed possible and where to count on deviation from the expected semantic overlap.
Keywords: angleščina; collocation; English; English language; free combination; kolokacija; predlog; preposition; prosta zveza; prototip; prototype; radial model; radialni model; Slovene; Slovene language; slovenščina